CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

If a root of the equation $$ax^2+bx+c=0$$ be reciprocal of a root of the equation $$a'x^2+b'x+c'=0$$, then?


A
(ccaa)2=(bacb)(abbc)
loader
B
(bbaa)2=(cabc)(abbc)
loader
C
(ccaa)2=(ba+cb)(ab+bc)
loader
D
None of the above
loader

Solution

The correct option is A $$(cc'-aa')^2=(ba'-cb')(ab'-bc')$$
1820935_1073671_ans_44f79ce2e1ac4ee6af768ea87ba51981.jpg

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More



footer-image